Citation footprints on the sands of time: An analysis of idea migrations in strategic management - Nerur, Sridhar; Rasheed, Abdul A.; Pandey, Alankrita (Strategic Management Journal, 2016)
We elucidate the intellectual progression of the strategic management field by examining knowledge flows to and from the Strategic Management Journal ( SMJ ) during the period 1980–2009. We provide a detailed mapping of the evolution of the intellectual structure of the field and identify its input‐output dependency relationships with other fields. Analysis of citation data using three analytic techniques: log‐multiplicative model, pathfinder analysis, and entropy analysis allow us to discern strategic management's influence on and engagement with other disciplines. The results show that, within the intellectual universe of strategic management, SMJ has played a central role, both as a source and storer of knowledge. We notice that, over time, there has been a decline in practitioner orientation, greater communication with finance and sociology, and increasing linkages with international business and entrepreneurship. Copyright © 2015 John Wiley & Sons, Ltd.